2016
DOI: 10.1055/s-0036-1585091
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Acromegaly Arising from a Pituitary Adenoma within the Bony Intersphenoid Septum of a Patient with Empty Sella Syndrome

Abstract: Objective  To describe the work-up and treatment of rare ectopic acromegaly caused by a biopsy-proven somatotroph pituitary adenoma located within the bony intersphenoid septum of a patient with empty sella syndrome (ESS).Methods  We report the presentation, clinical course, diagnostic work-up, and lesion localization and treatment challenges encountered in a 55-year-old patient, with a brief review of relevant literature.Results  A 55-year-old African-American man presented with acromegaly and ESS. Attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In fact, an alteration of PRL circadian rhythm has been described in PES, associated with a chronic or intermittent altered intracranial pressure: the nightly PRL increment is reduced or completely lacked in patients with intracranial hypertension, even just during the REM phase (47,48). Rarely, pituitary hypersecretion condition was described in patients with PES associated to ectopic GH-and ACTHsecreting pituitary adenomas (49,50), located within the midline intersphenoidal septum. dynamics and possible immune system reactions.…”
Section: Endocrinological Picturementioning
confidence: 99%
“…In fact, an alteration of PRL circadian rhythm has been described in PES, associated with a chronic or intermittent altered intracranial pressure: the nightly PRL increment is reduced or completely lacked in patients with intracranial hypertension, even just during the REM phase (47,48). Rarely, pituitary hypersecretion condition was described in patients with PES associated to ectopic GH-and ACTHsecreting pituitary adenomas (49,50), located within the midline intersphenoidal septum. dynamics and possible immune system reactions.…”
Section: Endocrinological Picturementioning
confidence: 99%
“…However, acromegaly in patients with PES is exceedingly rare and limited to a handful of case reports and a few retrospective studies. In a single retrospective study of 76 patients with ES, only 3 patients were diagnosed with acromegaly ( 9 , 15 , 16 , 17 , 18 ). Following this, three retrospective studies conducted between 2004 and 2017 reported acromegaly with ES in 20.3% ( 19 ), 22% ( 20 ), and 15.4% ( 21 ) of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There was consensus to assess the ectopic production of GH-releasing hormone (GHRH) in case of biochemical diagnosis of acromegaly and an image of empty sella (S12). Primary empty sella syndrome is frequently associated to GH deficiency; [18] thus, the coexistence of this image with acromegaly might be explained by the existence of GHsecreting pituitary microadenomas or an ectopic pituitary adenoma [19][20][21], or more likely, by an ectopic secretion of GHRH, usually by a bronchial carcinoid tumor [22][23][24]. Both of these explanations might apply in the case of a biochemical diagnosis of acromegaly and no tumor image in the pituitary gland MRI [22,25,26].…”
Section: Diagnosismentioning
confidence: 99%